PENTINGNYA SOFT SKILLS TERHADAP PENGEMBANGAN KARIR GEN Z BAGI SISWA/I SMK KARYA NASIONAL, KAB. KUNINGAN JAWA BARAT - Umi Hanik Makmuroh; Venny Oktaviany; Eka Ahadiyat Suryana; Nunung Kurniasih; Wati Rahayu (POLITEKNIK LP3I JAKARTA, 2024)
The aim of this Community Service (PKM) is to provide knowledge and skills regarding Soft Skills to students SMK Karya Nasional, Kab. Kuningan Jawa Barat. Especially in improving their skills through guidance in improving Soft Skills abilities. The prospect of improving Soft Skills aims to train personality, communication skills or personal attributes that are needed to be able to provide good performance in a job or business. The Soft Skills they process will make it easier for students to interact with the environment they enter. The activities of this community service program are to provide outreach to students at SMK Karya Nasional as Generation Z, providing guidance or counseling which can improve Soft Skills through many supportive activities. This was done as an effort to improve Soft Skills for generation z in order to face the era of industrial revolution 4.0